Low-temperature sintered Bi1-xSmxNbO4 microwave dielectrics. Issue 4 (April 2020) - Lim, Hyuk; Oh, Young-Jei
Abstract: The Bi1-x Smx NbO4 ceramics (x = 0 ∼ 0.1) was prepared by a conventional solid-state reaction at a low temperature from 900℃ to 960℃. The crystal structures of the Bi1-x Smx NbO4 ceramics were single orthorhombic (α-BiNbO4 ) phase at all sintering conditions. Dielectric constant (εr ), Quality factor (Q·f), and the Temperature coefficient of resonant frequency (τf ) were significantly affected by Sm 3+ substitution. The εr ranged from 42.79 ± 0.5 to 41.71 ± 0.5, with the highest Q·f value of 32, 100 ± 1605 GHz in the Bi1-0.99 Sm0.01 NbO4 ceramic. The Q·f values of the Bi1-x Smx NbO4 ceramics were improved compared to the BiNbO4 ceramics. The τf of the Bi1-x Smx NbO4 ranged from -2.3 ± 0.5 ppm/℃ to -11.4 ± 0.5 ppm/℃. The Clausius-Mossotti equation and additivity rule of dielectric polarizabilities were introduced in order to explain dependence of the dielectric constant as a function of Sm content. The τf of the Bi1-x Smx NbO4 ceramics with Sm content also was associated with the bond valence of the Bi1-x Smx NbO4 ceramics.